2013
DOI: 10.1088/1748-9326/8/2/025017
|View full text |Cite
|
Sign up to set email alerts
|

Riverine ecosystem services and the thermoelectric sector: strategic issues facing the Northeastern United States

Abstract: Major strategic issues facing the global thermoelectric sector include environmental regulation, climate change and increasing electricity demand. We have addressed such issues by modeling thermoelectric generation in the Northeastern United States that is reliant on cooling under five sensitivity tests to evaluate losses/gains in power production, thermal pollution and suitable aquatic habitat, comparing the contemporary baseline (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) with potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…For example, California has implemented 316(b) by establishing cooling system technology-based standards aimed at reducing withdrawals of ocean and estuarine surface water, which has tended to shift once-through ocean water cooling to non-water cooled or recirculating systems in the state [39]. Through section 316(a), the Clean Water Act also sets operationally relevant limits on temperature increases due to water use for cooling [40,41], which influences choices about cooling system technologies. Although variability in regional consumptive water intensity for electricity is related to circumstance (e.g.…”
Section: Policy Drivers and Implications Of Variability In Water Consmentioning
confidence: 99%
“…For example, California has implemented 316(b) by establishing cooling system technology-based standards aimed at reducing withdrawals of ocean and estuarine surface water, which has tended to shift once-through ocean water cooling to non-water cooled or recirculating systems in the state [39]. Through section 316(a), the Clean Water Act also sets operationally relevant limits on temperature increases due to water use for cooling [40,41], which influences choices about cooling system technologies. Although variability in regional consumptive water intensity for electricity is related to circumstance (e.g.…”
Section: Policy Drivers and Implications Of Variability In Water Consmentioning
confidence: 99%
“…11,[79][80][81] In response, environmental regulations in the US (Clean Water Act 1972) and Europe (European Fish Directive, Water Framework Directive) have set limits on water intake volumes and river temperature increases that result from power plant thermal loads. 82,83 In recent summers, warm river temperatures have triggered regulatory temperature limit thresholds, forcing some power plants to shut down or curb electricity generation, sometimes resulting in blackouts and costing consumers in the US tens of millions of dollars.…”
Section: Planning For Algal Systemsmentioning
confidence: 99%
“…Vulnerability studies have shown this could constrain electricity generation in Europe and the US. 81,98 In addition, droughts worldwide have already resulted in lower crop yields and higher food prices. A changing climate is projected to intensify such extreme events causing further constraints on the agriculture sector and crop growth for both biofuel and food production.…”
Section: Planning For Algal Systemsmentioning
confidence: 99%
“…In addition, OTbased plants rely on sufficiently cool river temperatures to maintain optimal thermal efficiency [13,14]. Previous electricity generation vulnerability studies have concentrated on climate and water resource change impacts, while thermal pollution assessments have had a unitary focus on determining the temperature rise on receiving waters [5,[15][16][17][18][19][20][21][22]. In regions where power plants are closely populated along rivers, thermal pollution from upstream plants may cause plant-toplant thermal interference and increase condenser inlet temperatures at downstream OT-based plants, potentially lowering thermal efficiencies and triggering CWA curtailments [23].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of incorporating higher spatial and temporal resolutions to reliably assess thermal pollution is also yet to be addressed. Thermal pollution and electricity generation vulnerability assessments across large domains are typically executed at a 0.5 • spatial resolution, although few have used higher resolutions (0.05 • , 0.125 • ) [5,16,17,20,21,[24][25][26]. Studies that use coarse spatial resolutions may misgauge the extent of thermal pollution as it forces placement of multiple plants inside a single grid cell and fails to capture finer-scale variations in river discharge, temperatures and thermal equilibration rates.…”
Section: Introductionmentioning
confidence: 99%